Life cycle assessment of concrete incorporating scrap tire rubber: comparative study - Medine, M. (2020)
At present, the environment suffers from two major problems, the first is the adverse effect of the production of the construction materials due to the resulting emissions and the second one is the increase of the consumption of the natural materials needed in the construction industry. There are interesting waste products such as the used tires that can be a resource of those materials to replace the natural resources in depletion. The use of scrap tire rubber to produce concrete in Algeria is not really an available technique. A life cycle assessment to compare an ordinary cement Portland concrete (Cref) and six rubberized concretes (CRm) and (CRg) from the environmental impact was carried out using ATHENA Estimator. The nine studied environmental impact categories are Climate change, Acidification potential, particulate matters, Eutrophication, Destruction of the stratospheric ozone layer, Photochemical ozone creation, Primary energy consumption, Consumption of fossil fuels, and Cumulative energy demand. The results inter-compared show that the energy demand and the generated emissions in the case of ordinary concrete are superiors than those of the rubberized concretes; concretes made with natural aggregates and 5, 7.5 and 10% of crumb rubber and coarse rubber aggregates (CRm) are more environmentally friendly than (CRg) mixtures made with natural aggregates and 5, 7.5 and 10% of coarse rubber aggregates. It is also concluded that the environmental impacts depend on the amount of substituted aggregates.